Developing the Art–Technology Intergenerational Community Program for Older Adults' Health and Social Connectedness - Seo, Jinsil Hwaryoung; Sungkajun, Annie; Garcia, Brittany (Frontiers in Public Health, 2021)
As the older adult population increases research investigating how to support their health and well-being has become more urgent. This paper discusses the development of the Art-Technology Intergenerational Community (ATIC) program for older adults in Bryan and College Station, Texas. The program’s purpose was to help improve older adult’s health, well-being and social connectedness. During the program, participants attended four sessions across four weeks creating interactive art projects such as Light-up Cards, Pop-up cards with Light, Interactive Light Painting, and Interactive Soft Circuit Ornaments. Preliminary studies allowed researchers to refine making materials by designing easy to follow fabricated circuit templates. Participants were able to create interactive art by using various materials such as LEDs, copper tape, coin-cell batteries, conductive thread and much more. A total of 18 participants aged 60-83 participated in the ATIC program. Participants were asked to complete pre and post study questionnaires which assessed older adults’ subjective health or well-being, feelings of intergenerational connectedness and attitude about art and technology. Video data was captured for qualitative analysis on the art creation process, cognitive health and social connectedness of the participants. Our findings show that those who participated in the ATIC program had improved perceptions of their own health and intergenerational relationships. There were also significant differences between pre and post study conditions for positive and negative affect. Qualitative results showed the program participants were engaged in the art-making process, creations helped to support intergenerational relationships with the student volunteers as well as their own family members.